2020
DOI: 10.1111/cge.13734
|View full text |Cite
|
Sign up to set email alerts
|

A paternally inherited non‐sense variant c.424G>T (p.G142*) in the first exon of XLαs in an adult patient with hypophosphatemia and osteopetrosis

Abstract: XLαs, the extra-large isoform of alpha-subunit of the stimulatory guanine nucleotidebinding protein (Gsα), is paternally expressed. The significance of XLαs in humans remains largely unknown. Here, we report a patient who presented with increased bone mass, hypophosphatemia, and elevated parathyroid hormone (PTH) levels. His serum calcium was in the lower limit of the normal range. Whole exome sequencing of this subject found a novel non-sense variant c.424G>T (p. G142*) in the first exon of XLαs, which was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The phenotypes associated with matUPD20 are similar to those observed in children with large paternal GNAS deletions (Aldred et al, 2002;Genevieve et al, 2005) and thus attributed largely to XLαs deficiency. Moreover, a recent study described an adult patient with hypophosphatemia and osteopetrosis who carried a nonsense mutation within the first XLαs exon (Chen et al, 2020). This defect was also paternally inherited, consistent with the evidence that XLαs is expressed from the paternal allele.…”
Section: Introductionsupporting
confidence: 67%
“…The phenotypes associated with matUPD20 are similar to those observed in children with large paternal GNAS deletions (Aldred et al, 2002;Genevieve et al, 2005) and thus attributed largely to XLαs deficiency. Moreover, a recent study described an adult patient with hypophosphatemia and osteopetrosis who carried a nonsense mutation within the first XLαs exon (Chen et al, 2020). This defect was also paternally inherited, consistent with the evidence that XLαs is expressed from the paternal allele.…”
Section: Introductionsupporting
confidence: 67%
“…39,40 Our group has previously reported that the Gnasxl first exon paternal point mutation c.424G > T (p.G142*) resulted in a nonsense mutation in XLαs and a synonymous mutation in ALEX in a proband; his father and daughter also did not have a suckling disorder. 10 A polymorphism in the first exon encoding XLαs and ALEX was found to reduce the affinity between XLαs and ALEX proteins, increasing the activation of XLαs on the platelet plasma membrane and leading to an increased bleeding tendency. However, some of those patients have feeding difficulties, hypotonia, growth retardation, mental retardation, and short fingers.…”
Section: The Effect Of Defective Expression Of Xlαs On Suckling Is St...mentioning
confidence: 99%
“…38 SaOS 2 cells transfected with an XLαs deletion mutant showed significantly reduced levels of cAMP after PTH stimulation compared to cells transfected with normal XLαs. 10 Moreover, the response times of cAMP production by activated XLαs and Gsα proteins following stimulation differed, and cells transfected with XLαs showed a significantly longer cAMP response than Gsα-transfected cells when induced by the parathyroid hormone analog M-PTH. In transfected cells, full-length human XXLαs was localized to the plasma membrane and mediated isoproterenol-and cholera toxin-stimulated cAMP accumulation.…”
Section: Structural and Functional Characteristics Of Xlαs Proteinsmentioning
confidence: 99%
See 2 more Smart Citations